2 Answers | Add Yours
You need to use the exponential laws, that helps you to evaluate the given exponential expression``, such that:
`y^x*y^(-x) = y^(x + (-x)) => y^x*y^(-x) = y^0 => y^x*y^(-x) = 1`
Raising to 4th power, yields:
`(y^x*y^(-x))^4 = 1^4 => (y^x*y^(-x))^4 = 1`
Hence, performing the indicated operations, using the exponentials laws, yields `(y^x*y^(-x))^4 = 1` .
we know this law of exponent.
`x^m xx x^n=x^(m+n) , `
So and " times mean multiply "
`(y^x xx y^-x)^4=(y^(x-x))^4`
We’ve answered 318,911 questions. We can answer yours, too.Ask a question